Outcomes of Bone Marrow Mononuclear Cell Transplantation for Neurological Sequelae Due to Intracranial Hemorrhage Incidence in the Neonatal Period: Report of Four Cases - Liem, Nguyen Thanh; Huyen, Truong Linh; Huong, Le Thu; Doan, Ngo Van; Anh, Bui Viet; Anh, Nguyen Thi Phuong; Tung, Dang Thanh (Frontiers in Pediatrics, 2020)
Aim: the aim of this study was to present primary outcomes of autologous bone marrow mononuclear cells (BMMNCs) transplantation to improve neurological sequelea in four children with intracranial hemorrhage (ICH) incidence during neonatal period. Methods: GMFM88 and modified Ashworth score were used to assess motor function and muscle spasticity before BMMNCs transplantation and after transplantation. Brain MRI was performed to evaluate brain morphology before and after BMMNCs transplantation. Bone marrow were harvested from anterior iliac crest puncture and BMMNCs were isolated using Ficoll gradient centrifugation. The microbiological testing, cell counting and hematopoietic stem cell (hHSC- CD34+ cell) analysis were performed, following which BMMNCs were infused intrathecally. Results: Improvement in motor function was observed in all patients after transplantation. In addition, muscle spasticity was reduced in all four patients. Conclusion: Autologous BMMNCs transplantation may improve motor function and reduce muscle spasticity in children with ICH incidence during neonatal period